HOMES OF MANY TONGUES: FAMILY LANGUAGE POLICY AND ENGLISH LITERACY IN MULTILINGUAL INDONESIA - Sadri, Idris (Philosophica: Jurnal Bahasa, Sastra, dan Budaya, 2025)
This study investigates the ways in which Family Language Policy (FLP) and home-based literacy practices mediate children’s English literacy development in multilingual Indonesian households. While English Language Teaching (ELT) scholarship has traditionally privileged school-based instruction, the role of families—particularly in contexts where Bahasa Indonesia coexists with regional languages such as Javanese or Sundanese—remains insufficiently theorized. Drawing on simulated mixed-method data, the study delineates three recurrent FLP orientations: structured (30%), emergent (50%), and passive (20%). The findings suggest that rather than adopting uniform strategies, families develop fluid, ideologically motivated practices that are profoundly shaped by sociocultural values, socioeconomic positioning, and translanguaging repertoires. Parental attitudes—ranging from positive to ambivalent or resistant— emerge as decisive in determining both the frequency and quality of children’s English exposure. Notably, even families with limited material resources exhibit considerable linguistic agency, incorporating English through media, storytelling, and bilingual scaffolding. By challenging deficit-oriented perspectives, this study demonstrates that children’s English literacy trajectories are constituted through social interaction, cultural negotiation, and multilingual creativity rather than material access alone. It argues for a reconceptualization of ELT frameworks that foreground the household as a dynamic and generative site of language learning and identity formation.